2012
DOI: 10.1021/es303191g
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol Analogues in Sediments from Industrialized Areas in the United States, Japan, and Korea: Spatial and Temporal Distributions

Abstract: Bisphenol analogues are used in the production of polycarbonate plastics and epoxy resins. Despite the widespread use of bisphenols, few studies have reported the occurrence of compounds other than bisphenol A (BPA) in sediment. In this study, concentrations and profiles of eight bisphenol analogues were determined using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) in sediments collected from several industrialized areas in the United States (U.S.), Japan, and Korea. The total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
141
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(147 citation statements)
references
References 56 publications
4
141
2
Order By: Relevance
“…Liao et al (2012) reports highest concentration of BPA was found in sediment from Korea (mean: 567, median: 6.02 μg kg − 1 dw), followed by Japan (8.17 and 8.30 μg kg −1 dw), and the USA (5.14 and 1.49 μg kg −1 dw). Bisphenol A concentration in sediment from Medway River, UK was reported in range of 7.7-56.1 μg kg −1 (dw) (Hibberd et al 2009).…”
Section: Distribution Of Bpamentioning
confidence: 97%
“…Liao et al (2012) reports highest concentration of BPA was found in sediment from Korea (mean: 567, median: 6.02 μg kg − 1 dw), followed by Japan (8.17 and 8.30 μg kg −1 dw), and the USA (5.14 and 1.49 μg kg −1 dw). Bisphenol A concentration in sediment from Medway River, UK was reported in range of 7.7-56.1 μg kg −1 (dw) (Hibberd et al 2009).…”
Section: Distribution Of Bpamentioning
confidence: 97%
“…Although scientists are just beginning to analyze the safety of BPS, studies suggest this compound is already pervasive in the environment, 5 in paper products, 6 and in the human body.…”
mentioning
confidence: 99%
“…It has been frequently detected in surface water (0-6840 ng L À1 ), 2 sediments (0.002-1970 ng g À1 dry weight), 3 sewage sludge (0.17-110 ng g À1 dry weight), 4 wastes such as human urine, 5,6 and daily products.…”
Section: Introductionmentioning
confidence: 99%